Mariana Smoluchowskiego ujęcie zasady przyczynowości w badaniach ruchów Browna - Zenon Eugeniusz Roskal (Zagadnienia Filozoficzne w Nauce, 2017)
Marian Smoluchowski solved the greatest scientific problem of his time. It was the explanation of the phenomenon of the Brownian motion. In the article, I show that Smoluchowski in fact in this explanation used an ontological interpretation of the causality principle, although in his writings he applied it also in the epistemological interpretation. This is understandable because in the scientific practice some kinds of ontological commitment are required.